Brain, Liver, and Serum Salusin-alpha and -beta Alterations in Sprague-Dawley Rats with or without Metabolic Syndrome - Citil, Cihan; Konar, Vahit; Aydin, Suleyman; Yilmaz, Musa; Albayrak, Serdal; Ozercan, Ibrahim Hanifi; Ozkan, Yusuf (Int Scientific Information, Inc, 2014)
Background: This metabolic syndrome (MetS) study was designed to investigate changes in expression of the neuropeptides salusin-alpha (Sal-alpha) and salusin-beta (Sal-beta) in brain and liver tissue in response to obesity and related changes induced by high-fructose diet and explored how these changes were reflected in the circulating levels of Sal-alpha and Sal-beta, as well as revealing how the lipid profile and concentrations of glucose and uric acid were altered. Material/Methods: The study included 14 Sprague-Dawley rats. The control group was fed ad libitum on standard rat pellets, while the intervention group was given water with 10% fructose in addition to the standard rat pellet for 3 months. Sal-alpha and Sal-beta concentrations in the serum and tissue supernatants were measured by ELISA, and immunohistochemical staining was used to demonstrate expression of the hormones in brain and liver. Results: Sal-alpha and Sal-beta levels in both the serum and the brain and liver tissue supernatants were lower in the MetS group than the control group. Sal-alpha and Sal-beta were shown by immunohistochemistry to be produced in the brain epithelium, the supraoptic nucleus of the hypothalamus, and the liver hepatocytes. Conclusions: The decrease in Sal-alpha and Sal-beta might be involved in the etiopathology of the metabolic syndrome induced by fructose.
Keywords: 14-3-3 Proteins; Liver Failure, Acute; Neuroendocrine Secretory Protein 7B2